Prinsip Pernikahan: Solusi Konflik Pascanikah (1 Korintus 7:3-5) - yatmini (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2023)
The first institution formed by God is the family. God formed the family for the good of mankind with the aim of the glory of God. However, sin destroys the relationship of the husband and wife formed by God. This study aims to look at the principles of marriage according to 1 Corinthians 7:3-5 and how to deal with conflicts between husband and wife after marriage. The research method used is content analysis method, which is to find biblical solutions for post-marital couples. Based on the content analysis of the text specified in this study, it was found that there is a relationship between the principle of marriage and the solution in dealing with post-marital conflicts, such as: 1) post-marital conflict solutions: a) fulfilling obligations to partners (7:3), b) not having power over his own body (7:4). In post-marital relations, husband and wife must have openness to one another as a form of mutual belonging. 2) How to resolve conflicts in the family (7:5): a) don't take away the rights of your spouse (7:5), b) make an agreement (7:5). 3) The purpose of resolving conflict (7:5): a) continue to rely on God, b) return to live together, c) so that the devil does not destroy the household. And these principles will strengthen the relationship between husband and wife in overcoming and resolving post-marital conflicts. ABSTRAK BAHASA INDONESIA Lembaga pertama yang menjadi bentukan Allah adalah keluarga. Allah membentuk keluarga untuk kebaikan manusia dengan tujuan kemuliaan Allah. Namun, dosa merusak relasi pasangan suami istri bentukan Allah tersebut. Penelitian ini bertujuan untuk melihat prinsip-prinsip pernikahan menurut 1 Korintus 7:3-5 dan bagaimana solusi menghadapi konflik pasangan suami istri pascanikah. Metode penelitian yang digunakan adalah metode analisis isi yaitu untuk menemukan solusi Alkitabiah bagi pasangan pascanikah. Berdasarkan analisis isi pada teks ditemukan bahwa ada hubungan antara prinsip pernikahan dengan solusi dalam menghadapi konflik pascanikah, seperti: 1) solusi konflik pascanikah: a) memenuhi kewajiban terhadap pasangan (7:3), b) tidak memiliki hak atas fisiknya sendiri (7:4). Dalam relasi suami istri pascanikah harus memiliki keterbukaan sebagai wujud saling memiliki. 2) Cara menyelesaikan konflik dalam keluarga (7:5): a) jangan merampas hak pasangan (7:5), b) mengadakan kesepakatan (7:5). 3) Tujuan menyelesaikan konflik (7:5): a) tetap mengandalkan Tuhan, b) kembali hidup bersama, c) supaya iblis tidak merusak rumah tangga. Dan prinsipprinsip tersebut akan memperkuat relasi pasangan suami istri dalam mengatasi dan menyelesaikan konflik pascanikah.